Residual biomass as resource – Life-cycle environmental impact of wastes in circular resource systems - Olofsson, Johanna; Börjesson, Pål (Journal of Cleaner Production, 2018)
Within an envisioned circular bio-based economy, a key component is the valorization of biomass wastes and residues into valuable products. If the commonly used method of life-cycle assessment (LCA) is applied to such products, an update and adaptation of LCA practice is needed regarding potentially outdated assumptions of residual resources as free from environmental impact. This paper therefore presents and discusses LCA approaches to evaluating residual biomass as resources, and implications of different approaches to LCA results and decision-making. Based on an analysis of 31 LCA studies of bio-based products, and on a model for recycling in LCA, we discuss alternatives to zero-burden assumptions for biomass residues. The studied literature shows a variety of approaches to assessing the impacts of residues, including views of relevant characteristics and causality in primary production systems, and intended use and interpretation of LCA results. In general, acknowledging upstream impacts through a simple model of recycling and allocation entails that the environmental characteristics of primary production systems reflect on by-products and residues. We argue that LCA studies of residue valorization must recognize the potential value of residues by considering upstream impacts, and thereby avoid both misconceptions of residues as per default environmentally preferable resources, and unintentional support for high-impact primary production systems. Residues as resources require this adaptation in LCA practice in order to avoid misguided decisions for a low-impact, bio-based and circular economy.
Keywords: Bioeconomy; By-product; Circular economy; LCA; Life-cycle assessment; Zero burden